Mechanism of turbulence modulation of sediment-laden flow for the case of equilibrium suspended-load transport - Xie, Haonan; Cai, Huiyi; Wang, Hao; Fu, Dabao; Xu, Naixing; Xu, Dongze (Frontiers in Physics, 2025)
The interphase interaction between water flow and sediment and particle collision in sediment laden flow will modulate the flow turbulence. Due to the complexity of suspended sediment movement, the mechanism of water-sediment interaction has always been a difficult point in the study, especially the modulation law of water-sediment interaction on flow turbulence has not reached a consistent conclusion. It is of great significance for the study of sediment laden flow to optimize the construction of the numerical model of water and sediment. In this study, a Euler solid–liquid two-phase flow model was used to investigate the effects of drag force, density gradient, and particle collisions generated by natural sand and plastic sand on flow characteristics under the condition of different sediment concentrations for the case of equilibrium suspended-load transport, so as to determine the degree of influence of various factors in the numerical simulation process on the turbulent flow properties. Results showed that the presence of sediment particles changes the flow velocity, sediment concentration distribution, and turbulent energy distribution, and that such effects strengthen with increase in sediment concentration. The effects of drag force and particle collisions on the resistance coefficient and on flow velocity are dominant. The drag force tends to reduce the resistance coefficient and increase flow velocity, whereas particle collisions produce the opposite effect. The density gradient and particle collisions are the dominant factors affecting the turbulent diffusion coefficient of the suspended load and the vertical distribution of the sediment concentration. However, they produce opposite effects that partially cancel each other. With increase in sediment concentration, the effect of sediment particles on the turbulence of sediment-laden flow increases; the drag force and density gradient inhibit turbulence, and particle collisions promote turbulence.